Das Gelingen der künstlichen Natürlichkeit - Mitscherlich-Schönherr, Olivia (GRENZGÄNGE, 2021)
It is becoming increasingly possible to fundamentally intervene into human life using disruptive biotechnologies. On the other side, artificial intelligence is advancing rapidly. In this twofold development, the boundaries between human nature and technology are being blurred. This has provoked fundamental questions about what it is to be human, with which this volume engages interdisciplinarily.